2018
DOI: 10.21743/pjaec/2018.06.10
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Acrylamide in Branded and Non-branded Potato Chips by using High Performance Liquid Chromatography

Abstract: Acrylamide, a starchy food process contaminant is carcinogenic, neurotoxic and genotoxic substance. It is formed at temperatures of 100°C-220°C. The chips are very popular food items especially among children. Deep Frying of chips may cause production of acrylamide. The presence of acrylamide in chips may result in severe health issues in consumers especially in children. By keeping this aspect in view, the present study was conducted to determine acrylamide in different potato chips of branded and non-branded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In recent study, it was found that in non-branded chips obtained from a local shop of Lahore, Pakistan, acrylamide was present in considerable amount i.e. 2649.80μg/kg [87].…”
Section: Hepatotoxicity Of Acrylamidementioning
confidence: 99%
“…In recent study, it was found that in non-branded chips obtained from a local shop of Lahore, Pakistan, acrylamide was present in considerable amount i.e. 2649.80μg/kg [87].…”
Section: Hepatotoxicity Of Acrylamidementioning
confidence: 99%